STRAIN DIFFERENCES IN TWO SPECIES OF CALLOSOBRUCHUS (COLEOPTERA: BRUCHIDAE) DEVELOPING ON SEEDS OF COWPEA {VIGNA UNGUICULATA (L.)} AND GREEN GRAM {V. RADIATA (L.)} - RENNIE ROESLI (BIOTROPIA, 1991)
Ovipositional behaviour, development period, and density effect on adult survival of C. maculatus strains from  Indonesia, Nigeria, and Yemen, and C. chinensis strains  from  Indonesia and Kenya on cowpea and green gram were studied at 20°C and 70% relative humidity. Variations on ovipositional behaviour were found among C. maculatus as well as among C. chinensis strains. Variations on developmental period were found only among C. maculatus strains. The developmental period of Callosobruchus spp. was shorter on green gram than that on cowpea. Density effect was remarkably found only on  adult survival of C. maculatus Yemen strain. These  results make  useful  contribution  to  the species  biology,  and  have  important  implication  if  strains  of  these  species  are  accidentally  imported  to countries, or when new legume crops are introduced.